Introduction: Female Perspectives in Commercial and Consumer Law - Hawkins, Jim (Columbia Journal of Gender and Law, 2016)
Over the past several decades, female perspectives on commercial and consumer law have played an increasingly important role in the legal literature on credit, debt, and commerce. On the one hand, now that women are permitted a place in legal academia, many more women have made contributions to these scholarly fields. But also, the literature has increasingly engaged feminist thought, highlighting the challenges women face interacting with credit. As one prominent example of the special risks that women experience, consider fringe consumer credit markets. The majority of people taking out payday loans—those short-term loans for small amounts with high costs —are women. Other fringe credit products are the same. Women make up a majority of pawn shop customers, title lending customers, and rent-to-own customers.